Knowledge of cardiovascular disease risk in rheumatoid arthritis patients before and after educational intervention from a Southeast Asia country: Malaysia - Boon Ching TEOH; Syed Azhar SYED SULAIMAN; Bee Eng TAN (Archives of Rheumatology, 2021)
Objectives: This study aims to improve knowledge on cardiovascular disease (CVD) risk among rheumatoid arthritis (RA) patients using a multi- language leaflet tailored to our multi-ethnic patient population. Patients and methods: This was a prospective study conducted in Hospital Pulau Pinang, Malaysia, between March 2015 and June 2015. Educational intervention was provided to 96 patients (11 males, 85 females; mean age 52.4±12.9 years; range, 20 to 83 years) who fulfilled the inclusion/exclusion criteria. Questionnaires to assess knowledge of CVD risk were given to patients to be answered before reading the informative leaflet, after one hour of intervention, and during their next follow-up three months from the intervention. Both the informative leaflet and questionnaires were prepared in English and then translated into Malay and Chinese languages to suit the need of local patients. Results: Our results showed that RA patients had good knowledge at baseline regarding risk of smoking, hypertension, and hyperlipidemia on increasing CVD risk and that exercise would not damage their joints. However, they had low knowledge at baseline regarding the amount of exercise needed for lower CVD risks and risk of CVD with use of anti-inflammatory drugs in RA. Total knowledge score increased significantly from baseline immediately after educational intervention. However, total knowledge score decreased after three months compared to immediate post- intervention phase while it was still significantly higher compared to baseline. The improvement was most obvious for knowledge regarding anti- inflammatory drugs and CVD risk and knowledge regarding the number of flares and CVD risk. Our study did not find any significant association between demographic characteristics and traditional cardiovascular risk factors with knowledge of CVD risk. Conclusion: Rheumatoid arthritis patients have low knowledge regarding their CVD risk related to their disease. The intervention of providing an informative leaflet effectively improved the knowledge of this group of patients on CVD risk particularly in the field related to RA-specific risk.